Effects of milk casein-derived tripeptides Ile-Pro-Pro, Val-Pro-Pro, and Leu-Pro-Pro on enzymes processing vasoactive precursors in vitro - Lehtinen, Risto; Jauhiainen, Tiina; Kankuri, Esko; Lindstedt, Ken; Kovanen, Petri T.; Kerojoki, Outi; Korpela, Riitta; Vapaatalo, Heikki (Arzneimittelforschung, 2010)
Milk-based drinks containing casein-derived tripeptides isoleucine-proline-proline (Ile-Pro-Pro) and valine-proline-proline (Val-Pro-Pro) have been shown topossess antihypertensive and vascularendothelium-protecting properties in hy-pertensive animal models. Furthermorein clinical intervention trials they reduceblood pressure and arterial stiffness. Theexact mechanisms are not known, but inhibition of angiotensin converting enzyme 1 (ACE1) has been suggested mainlyto mediate these beneficial effectsThe present study investigated the in vitro effects of three tripeptides: Ile-Pro-Pro, Val-Pro-Pro and leucine-proline-proline (Leu-Pro-Pro) on four reninangiotensin system enzymes: ACE1ACE2, chymase, and cathepsin G. Also their effects on arginase I, a critical enzyme in L-arginine-nitric oxide pathway were studiedIt was shown, apparently for the firsttime, that the inhibitory effects of Ile-Pro-Pro, Val-Pro-Pro and Leu-Pro-Pro on ACE1 at micromolar concentrations arecompetitive in nature. Therefore the efficacy of inhibition is largely dependent onthe amount of substrate present. Inhibition of ACE2 and arginase I was reachedonly at concentrations three orders of magnitude greater. No inhibition of chymase and cathepsin G was observed by the tripeptidesThe findings support the hypothesis that Ile-Pro-Pro, Val-Pro-Pro and Leu-Pro-Pro act favourably on blood pressure mainly by selective inhibition of ACE1.
Keywords: Angiotensin-converting enzyme; Arginas; Ile-Pro-Pro; Leu-Pro-Pro; Selective inhibition; Val-Pro-Pro